P728 Efficacy of anti-TNF treatment in patients with refractory ulcerative proctitis: Results from a French retrospective multi-centre national cohort. (16th January 2018) - Pineton de Chambrun, G; Amiot, A; Bouguen, G; Viennot, S; Altwegg, R; Louis, E; Collins, M; Fumery, M; Poullenot, F; Armengol, L; Buisson, A; Abitbol, V; et al.
Abstract: Background: Management of patients with ulcerative proctitis (UP) refractory to conventional treatment is challenging. Data regarding efficacy of anti-TNF monoclonal antibodies are lacking as UP patients are systematically excluded from randomised clinical trials. The aim of our study was to evaluate the efficacy of anti-TNF for the treatment of patients with refractory UP. Methods: We performed a retrospective multi-centre study in 16 French and Belgian tertiary referral centres including all consecutive patients with UP (< 20 cm from the anal verge) refractory to conventional and/or immunosuppressive drugs treated with one anti-TNF monoclonal antibody from October 2001 to February 2017. Primary endpoint was the clinical response to treatment defined by the judgement of the referring physician and graded as follow: no response, partial response and remission. Persistence of treatment, hospitalisation and surgery during the follow-up were also analysed. When available Mayo score and UCEIS were collected. Results: In total, 95 patients with refractory UP (46F, 48M) and treated with anti-TNF were included with a median follow-up of 30 (IQR: 14.6–57.9) months. Previously to anti-TNF, 83% (79/95) of the patients were treated with topical steroids, 85% (81/95) with systemic steroids, 96% (91/95) with topical 5-aminosalicylic acids (5-ASA), 94% (89/95) with oral 5-ASA, 60% (57/95) with thiopurines, 8% (8/95) with methotrexate and 5% (5/95) with cyclosporin. Mean Mayo clinical subscore before anti-TNF was 5.86 ± 1.89. Median delay between UP diagnosis and anti-TNF start was 44 (18.4–110) months. 50% (47/95) of the patients were treated with infliximab, 39% (37/95) with adalimumab and 11% (11/95) with golimumab. Anti-TNF was associated to thiopurines in 41% (39/95) of the cases. Globally, 75% (69/92) of the patients had at least a partial response, 50% (46/92) a remission and 25% (23/92) no response to anti-TNF. Mayo clinical subscore significantly decreased from baseline to 12 week evaluation (5.9 ± 1.8 vs. 2.5 ± 2.5, p < 0.001). During follow-up, 11% (9/85) of the patients were hospitalised for a flare of their UP and 5% (4/85) had a coloproctectomy with J-pouch anastomosis. The cumulative probability of anti-TNFα failure free survival in anti-TNF primary responders was 97% ± 2% at 6 months, 82% ± 5% at one year and 75% ± 6% at 2 years. In multivariate analysis, concomitant therapy with thiopurines at baseline was the only clinical factor associated to clinical remission (OR 2.494; 95% CI: 0.161–1.790, p = 0.036). Conclusions: Clinical remission was achieved in 50% of the refractory UP patients treated with an anti-TNF. Concomitant thiopurine therapy was associated with an increased efficacy of the anti-TNF treatment.